PERAN BLOCKCHAIN DALAM MEMBANGUN KEPERCAYAAN DAN TRANSPARANSI DALAM BISNIS MODERN - Yulia Fitri; Moza Anastasya (CV. Denasya Smart Publisher, 2025)
This research aims at how blockchain technology builds trust and transparency in modern business. This study conducts descriptive qualitative research involving thematic analysis of secondary data. Blockchain systems can be found in various areas of business, especially in finance and logistics, and this is the subject of research. The data was collected through literature research over the past five years, which included relevant scientific articles and journals. Data analysis is carried out with a thematic approach to find key themes such as transparency, efficiency, and trust. In addition, problem collection, literature research, secondary data collection, and data analysis are also carried out. The results of the study show that blockchain minimizes the risk of data manipulation and increases transparency through the recording of irreversible transactions. The study shows that blockchain has great potential to increase trust and transparency in modern businesses, although its implementation requires cross-sector cooperation.